Media Informasi Tentang Komplementer Pada Masa Kehamilan Di Desa Sigam Kotabaru - Norani Norani; Ika Friscila; Fadhiyah Noor Anisa; Aida Fitriani; Hartinah Hartinah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Complementary therapy is known as traditional therapy combined in modern medicine. Complementary is the use of traditional therapy into modern medicine. When pregnancy occurs, the entire genetic system will experience fundamental changes so that it can support the development and growth of the fetus in the womb. Based on the analysis carried out by the service team, the community in Sigam Village knows that there is traditional medicine to deal with complaints during pregnancy, but not all mothers know the truth of this information in terms of medical science. This causes people to hesitate to choose complementary therapies. The information media created is a poster containing information about complaints during pregnancy and complementary solutions. This is very well received by the public because the media is interesting and easy to understand.